2017
DOI: 10.1371/journal.pone.0177639
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the SUMO E3 ligase PIAS1 as a potential survival biomarker in breast cancer

Abstract: Metastasis is the ultimate cause of breast cancer related mortality. Epithelial-mesenchymal transition (EMT) is thought to play a crucial role in the metastatic potential of breast cancer. Growing evidence has implicated the SUMO E3 ligase PIAS1 in the regulation of EMT in mammary epithelial cells and breast cancer metastasis. However, the relevance of PIAS1 in human cancer and mechanisms by which PIAS1 might regulate breast cancer metastasis remain to be elucidated. Using tissue-microarray analysis (TMA), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
1
42
1
Order By: Relevance
“… 216 Moreover, sumoylation of SnoN by PIAS1 has an inhibitory effect on the invasive capacity of MDA-MB231 cells. 288 Particularly for SnoN, it has been reported that this protein regulates cell differentiation in normal skin and in benign skin tumors, but it promotes squamous cell carcinoma. 289 SnoN induces proliferation of ovarian cancer cells, whereas it promotes cell cycle arrest and senescence in non-transformed ovarian epithelial cells.…”
Section: Regulation Of Tgf-β/smad Signaling By Ski and Snonmentioning
confidence: 99%
“… 216 Moreover, sumoylation of SnoN by PIAS1 has an inhibitory effect on the invasive capacity of MDA-MB231 cells. 288 Particularly for SnoN, it has been reported that this protein regulates cell differentiation in normal skin and in benign skin tumors, but it promotes squamous cell carcinoma. 289 SnoN induces proliferation of ovarian cancer cells, whereas it promotes cell cycle arrest and senescence in non-transformed ovarian epithelial cells.…”
Section: Regulation Of Tgf-β/smad Signaling By Ski and Snonmentioning
confidence: 99%
“…Overall, studies have revealed that each of PIAS1 and TIF1γ act via SnoN SUMOylation to suppress TGFβ-induced EMT in two-dimensional or three-dimensional culture systems [ 14 , 58 ] ( Figure 3 and Figure 4 ). Data also suggest that the PIAS1-SnoN SUMOylation axis suppresses TGFβ-induced invasive growth of 3D-breast cancer cell-derived organoid system [ 59 ] ( Figure 3 and Figure 4 ). Consistently, PIAS1 acts in a SUMO-E3 ligase-dependent manner to suppress the rate of breast-cancer cell-derived metastatic growth in a xenograft model [ 74 ].…”
Section: Sumoylation Of Tgfβ Pathway Signal Transducersmentioning
confidence: 99%
“…Consistently, PIAS1 acts in a SUMO-E3 ligase-dependent manner to suppress the rate of breast-cancer cell-derived metastatic growth in a xenograft model [ 74 ]. In order to promote EMT and invasive growth, data suggest that TGFβ, in turn, reduces the protein abundance of PIAS1 and proportion of SUMOylated SnoN in non-transformed mammary epithelial cells and breast carcinomas [ 14 , 59 ]. These data thus suggest the existence of an interplay between TGFβ signaling and PIAS1-SnoN SUMOylation axis in controlling EMT and potentially cancer invasion and metastasis.…”
Section: Sumoylation Of Tgfβ Pathway Signal Transducersmentioning
confidence: 99%
See 2 more Smart Citations